Mapping Protein–Protein Interactions within a Stable Complex of DNA Primase and DnaB Helicase from Bacillus stearothermophilus() - Bird, Louise E. (2000)
For the first time, we demonstrate directly a stable complex between a bacterial DnaG (primase) and DnaB (helicase). Utilizing fragments of both proteins, we are able to dissect interactions within this complex and provide direct evidence that it is the C-terminal domain of primase that interacts with DnaB. Furthermore, this C-terminal domain is sufficient to induce maximal stimulation of the helicase and ATPase activities of DnaB. However, the region of DnaB that interacts with the C-terminal domain of primase appears to comprise a surface on DnaB that includes regions from both of the previously identified N- and C-terminal domains. Using a combination of biochemical and physical techniques, we show that the helicase–primase complex comprises one DnaB hexamer and either two or three molecules of DnaG. Our results show that in Bacillus stearothermophilus the helicase–primase interaction at the replication fork may not be transient, as was shown to be the case in Escherichia coli. Instead, primase appears to interact with the helicase forming a tighter complex with enhanced ATPase and helicase activities.